THE SOROKIN MULTIDIMENSIONAL INVENTORY OF LOVE EXPERIENCE (SMILE): DEVELOPMENT, VALIDATION, AND RELIGIOUS DETERMINANTS - Levin, Jeffrey S. (Review of religious research, 2010)
This paper describes the development and validatin of the Sorokin Multidimensional Inventory of Love Experience (SMILE), a 24-item scale based on the writing of sociologist Pitirim Sorokin. The SMILE contains six subscales of four items each, corresponding to what Sorokin termed the religious, ethical, ontological, biological, psychological, and social domains of love. Through confirmatory factor analysis, all factor loadings were found to be strong and statistically significant. A model specifying intercorrelations among all subscales exhibited good overall fit, although biological love was only weakly related to the other factors. Finally, through hierarchical OLS regression, religious measures were found to be significant determinants of scores on five of six subscales. This confirms Sorokin's hypothesis that affirming the experience of love is in part a function of religiousness. The SMILE promises to broaden the scope of social research on love and to promote investigation of this neglected psychosocial construct.